2002
DOI: 10.1002/ijc.10626
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus antagonizes the antiproliferative activity of transforming growth factor‐β but does not abolish its signaling

Abstract: TGF-␤ induces apoptosis and inhibits the proliferation of EBV-negative B-lymphoma cell lines. In contrast, EBV-immortalized B cells are resistant to both the proapoptotic and the antiproliferative activities of TGF-␤. We have generated a lymphoblastoid cell line, in which we can switch on and off the EBV-specific transcriptional program driven by EBNA2. When these cells express the EBNA2-driven phenotype, they are resistant to TGF-␤-mediated growth arrest. We used this cell line to readdress the question of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Various mechanisms by which EBV confers resistance to TGF-␤ have been proposed (for a review, see reference 19), including a decrease in the level of TGF-␤ receptors (78,79,91). Elsewhere, however, it has been shown that the EBV Lat III program, but not c-MYC, preferentially protects P493-6 cells from the antiproliferative effect of TGF-␤1 (92). Furthermore, the same study ruled out the abolition of TGF-␤1 apoptotic signaling, cyclin D2, EBV lytic cycle activation, and secondary genetic events as potential contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms by which EBV confers resistance to TGF-␤ have been proposed (for a review, see reference 19), including a decrease in the level of TGF-␤ receptors (78,79,91). Elsewhere, however, it has been shown that the EBV Lat III program, but not c-MYC, preferentially protects P493-6 cells from the antiproliferative effect of TGF-␤1 (92). Furthermore, the same study ruled out the abolition of TGF-␤1 apoptotic signaling, cyclin D2, EBV lytic cycle activation, and secondary genetic events as potential contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…EBNA-2 transactivates the anti-apoptotic gene BFL-1 (BCL2A1, GenBank: NM_004049) in complex with RBP-Jj [22]. EBNA-2 can also inhibit the pro-apoptotic and anti-proliferative functions of the transforming growth factor beta 1 (TGFB1, GenBank: NP_000651) cytokine, as shown in the EBNA-2 inducible EREB system [23]. The EBNA3 family proteins are also increasingly involved in protection against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV miR-UL22A Downregulates SMAD3 to Allow Viral Reactivation in CD34 + HPCs Although HCMV-induced TGF-b exhibits myelosuppressive effects on uninfected CD34 + HPCs, the effects of the cytokine on latently infected HPCs are unknown. Since TGF-b can negatively affect the growth of other viruses (Campion et al, 2014;Chiu et al, 2012;Choi et al, 2015;Di Bartolo et al, 2008;DiMaio et al, 2014;Fukuda et al, 2002;Fukuda and Longnecker, 2004;Horndasch et al, 2002;Inman and Allday, 2000;Lei et al, 2012;Lo et al, 2010;Mori et al, 2003;Morris et al, 2016;Prokova et al, 2002;Seo et al, 2005;Tomita et al, 2004;Wood et al, 2007), we hypothesized that HCMV protects infected cells from the negative effects of TGF-b signaling by manipulating components of the TGF-b signaling pathway. To test this hypothesis, we mock-or HCMV-infected primary CD34 + HPCs for 48 h and isolated a pure population of viable, CD34 + , GFP + HPCs.…”
Section: Hcmv Mir-us5-2 Is Sufficient To Induce Expression Of Tgf-b and Myelosuppression In Cd34 + Hpcsmentioning
confidence: 99%